2015
DOI: 10.1002/nau.22929
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of reoperation after sacral neuromodulation: A single institution evaluation of over 400 patients

Abstract: In this largest known series to date, one third of the patients required reoperation and the most common reason was lack of efficacy/worsening symptoms. Ongoing study is needed as the technology continues to evolve. Neurourol. Urodynam. 36:354-359, 2017. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 16 publications
1
31
0
1
Order By: Relevance
“…The literature is inconsistent regarding an assumed association between BMI and efficacy during PNE for both FI and UI, but increased rates of reoperations and complications have been described in SNM patients with a lower BMI [37][38][39][40][41]. While series exploring the predictors of SNM for FI have failed to show an association between BMI and outcome [8,29,30], a relation between low BMI and unfavourable outcome, as shown in our study, has also been demonstrated in urological patients [37,38,41] and children [39]. Bilateral migration of tined leads in a thin patient has been thoroughly discussed by Kessler et al [41].…”
Section: Discussionmentioning
confidence: 99%
“…The literature is inconsistent regarding an assumed association between BMI and efficacy during PNE for both FI and UI, but increased rates of reoperations and complications have been described in SNM patients with a lower BMI [37][38][39][40][41]. While series exploring the predictors of SNM for FI have failed to show an association between BMI and outcome [8,29,30], a relation between low BMI and unfavourable outcome, as shown in our study, has also been demonstrated in urological patients [37,38,41] and children [39]. Bilateral migration of tined leads in a thin patient has been thoroughly discussed by Kessler et al [41].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective longitudinal study, investigators found that among other factors, decreased BMI, had a higher risk of reoperation. 41 In another study, the results suggested that lower BMI might predict reoperation, however, BMI was not significant when adjusted for other covariates. 42 A more recent retrospective review also failed to find any associations between obesity and reoperation.…”
Section: Sacral Neuromodulationmentioning
confidence: 95%
“…The study model estimated that a woman with a BMI of 25 would have a roughly 50% greater chance of achieving ≥50% improvement in UUI compared with a BMI of 35. In a prospective longitudinal study, investigators found that among other factors, decreased BMI, had a higher risk of reoperation . In another study, the results suggested that lower BMI might predict reoperation, however, BMI was not significant when adjusted for other covariates .…”
Section: Treatment Of Oab and Uui—does Obesity Affect Outcome?mentioning
confidence: 97%
“…10,11 Although pelvic pain has not previously been reported as a negative predictor for SNM success, it has been shown to predict reoperation. 12 Several baseline characteristics were found to have no association with successful stage 2 SNM implant. These included age, comorbidities, BMI, presence of urodynamic DO, history of neurogenic bladder, and surgical characteristics.…”
Section: Discussionmentioning
confidence: 95%
“…In other studies, SNM has been explored as an off label therapy for indication of pelvic pain . Although pelvic pain has not previously been reported as a negative predictor for SNM success, it has been shown to predict reoperation …”
Section: Discussionmentioning
confidence: 99%